2022
DOI: 10.1253/circj.cj-21-0326
|View full text |Cite
|
Sign up to set email alerts
|

Different Determinants of the Recurrence of Atrial Fibrillation and Adverse Clinical Events in the Mid-Term Period After Atrial Fibrillation Ablation

Abstract: matched or adjusted patients who did and did not undergo ablation, 4-6 and several randomized control trials 7-9 have P ulmonary vein isolation (PVI) is an accepted therapy for atrial fibrillation (AF), 1 and is widely performed worldwide. Development of ablation and mapping systems has increased the efficacy and safety of AF ablation. 2,3 Recent observational studies comparing Editorial p ????

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
2
12
0
1
Order By: Relevance
“…This may due to its association with structural remodeling in AF. A similar conclusion was also found by Mesquita et al 21 and Wang et al 37 Type of AF was a commonly used predictor for AF recurrence prediction in some studies, 7,21,30-33, 38 and these studies indicated that non-PAF patients had a higher risk of recurrence. This conclusion is also compatible with our results, as shown in Supplementary Table 3, where the proportions of patients with non-PAF in the low-, mediumand high-risk groups are 0%, 21.4% and 88.5%, respectively.…”
Section: Discussionsupporting
confidence: 79%
“…This may due to its association with structural remodeling in AF. A similar conclusion was also found by Mesquita et al 21 and Wang et al 37 Type of AF was a commonly used predictor for AF recurrence prediction in some studies, 7,21,30-33, 38 and these studies indicated that non-PAF patients had a higher risk of recurrence. This conclusion is also compatible with our results, as shown in Supplementary Table 3, where the proportions of patients with non-PAF in the low-, mediumand high-risk groups are 0%, 21.4% and 88.5%, respectively.…”
Section: Discussionsupporting
confidence: 79%
“…It also enables more precise management of patients after ablation, including the duration of antiarrhythmic drug therapy, monitoring for asymptomatic recurrence. Previous studies have shown that dilated LA increases the risk of AF recurrence after single ablation [ 31 , 32 ]. In our study, we also found the LAd ≥ 4.5 cm and AF duration ≥ 24.5 months were the recurrence predictors after PVI-plus linear ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, PerAF in the 2014–2015 group might have had the worst AF/AT freedom rate, and therefore, the worst clinically relevant events, but no difference was noted among the three time period groups. The clinical impact of ablation may have been dependent on not only AF/AT recurrence, but also the baseline characteristics and post‐ablation AADs and OACs 40 . The lowest continuation rate of AADs but highest rate of OACs after ablation at the physicians' discretion in the 2016–2017 group may also have reflected the fear of a stroke risk when AF/AT recurrences occur.…”
Section: Discussionmentioning
confidence: 99%